The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1063/1.1839274
|View full text |Cite
|
Sign up to set email alerts
|

Chip-scale atomic magnetometer

Abstract: Using the techniques of microelectromechanical systems, we have constructed a small low-power magnetic sensor based on alkali atoms. We use a coherent population trapping resonance to probe the interaction of the atoms’ magnetic moment with a magnetic field, and we detect changes in the magnetic flux density with a sensitivity of 50pTHz−1∕2 at 10Hz. The magnetic sensor has a size of 12mm3 and dissipates 195mW of power. Further improvements in size, power dissipation, and magnetic field sensitivity are immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
206
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(207 citation statements)
references
References 17 publications
0
206
0
1
Order By: Relevance
“…Another approach, particularly appealing for future mass production of miniaturized lowcost magnetometers, is manufacturing of an integrated sensor package incorporating a VCSEL laser, an alkalivapor cell, optics, and a detector using the wafer production techniques well developed by the semi-conductor industry. The first magnetometers based on this approach with a grain-of-rice sized integrated sensor have been recently constructed [56,57], demonstrating a sensitivity of 50 pT/ √ Hz, with anticipated improvement by several orders of magnitude with further optimization.…”
Section: Additional Characteristics Of a Magnetometermentioning
confidence: 99%
“…Another approach, particularly appealing for future mass production of miniaturized lowcost magnetometers, is manufacturing of an integrated sensor package incorporating a VCSEL laser, an alkalivapor cell, optics, and a detector using the wafer production techniques well developed by the semi-conductor industry. The first magnetometers based on this approach with a grain-of-rice sized integrated sensor have been recently constructed [56,57], demonstrating a sensitivity of 50 pT/ √ Hz, with anticipated improvement by several orders of magnitude with further optimization.…”
Section: Additional Characteristics Of a Magnetometermentioning
confidence: 99%
“…Without any steps taken towards optimization, the current M z magnetometer sensitivity is $20 nT/ͱHz. We expect that by (1) adding magnetic shields around the resonance cell, (2) reducing the field inhomogeneities introduced by the resonance cell heater, 19 and (3) changing to the M x interrogation technique, 30 the sensitivity can be greatly improved to create a high-performance miniature DR magnetometer. It has been previously shown that using lamps or lasers as pumping light sources result in comparable magnetometer performances.…”
Section: Rb and 87mentioning
confidence: 99%
“…18 Most of the recent miniature demonstrators and devices however typically use a laser diode (VCSEL-Vertical Cavity Surface Emitting Laser) as the pumping light source to emit the required alkali D-lines. 10,19 This was mainly because the inductively coupled glass-blown (GB) alkali discharge lamps, with their hardto-integrate cylindrical/spherical geometry and high power consumption (several Watts), could not be scaled down to meet the size and power requirements of miniature clocks, and because the Coherent Population Trapping (CPT) scheme often employed for miniature atomic clocks requires two phase-coherent light fields that is usually provided by a laser source. 20 VCSELs are compact, energy efficient, and operate at low power, and hence were suitable choices.…”
mentioning
confidence: 99%
“…In recent years, however, significant technical advances have enabled atomic magnetometers to achieve sensitivities rivaling [13,14,15,16,17,18] and even surpassing [19] that of most SQUID-based magnetometers. Atomic magnetometers have the intrinsic advantage of not requiring cryogenic cooling, and efficient methods for microfabrication of atomic magnetometers (with dimensions ∼ 1 mm) have recently been developed [20,21]. Thus atomic magnetometers offer the possibility of compact, affordable, and portable ultra-sensitive magnetic sensors.…”
Section: Introductionmentioning
confidence: 99%